Measuring supply chain management practices - de Sousa Jabbour, Ana Beatriz Lopes [UNESP]; Filho, Alceu Gomes Alves; Viana, Adriana Backx Noronha; Jabbour, Charbel José Chiappetta (Emerald, 2011)
Purpose: This paper aims to perform an empirical investigation about the constructs and indicators of the supply chain management practices framework. Design/methodology/approach: The measuring framework proposed is based on a survey that was carried out on 107 Brazilian companies. Statistical techniques were employed to verify, validate, and test the reliability of the constructs and their indicators. To validate this framework principal component analysis and structural equation modeling techniques were used. Findings: In general, previous studies suggest six constructs for measuring the supply chain management practices framework. However, in this study a framework was achieved with four constructs of supply chain management practices, namely, supply chain (SC) integration for production planning and control (PPC) support, information sharing about products and targeting strategies, strategic relationship with customer and supplier, and support customer order. This framework has adequate levels of validity and reliability. Research limitations/implications: The main limitation of this study was that only a small sample of companies in a single sector and country were surveyed, and therefore there needs to be further research considering the special conditions in other countries. Originality/value: This study investigated statistically set indicators to discuss the topic supply chain management practices. The framework obtained has good quality of validity and reliability indicators. Thus, an alternative framework has been added to measure supply chain management practices, which is currently a popular topic in the supply chain mainstream literature. Both defined constructs and the validated indicators can be used in other studies on supply chain management. © Emerald Group Publishing Limited.
Keywords: Brazil; Performance measurement (quality); Supply chain management; Working practices